Особливості якісного та кількісного аналізу ризиків підприємств олійно-жирової галузі - Жадан, Юлія Володимирівна (НТУ "ХПІ", 2017)
Обґрунтовано особливості якісного аналізу економічних ризиків, до яких віднесено фактори ризиків, визначення їх рівня, ідентифікація ризиків. Визначено особливості кількісного аналізу ризиків: вибір методів кількісної оцінки ризиків, оцінка ризикозахищеності підприємств і встановлення зон ризику. Встановлені на підставі аналізу показників кількісної оцінки ризиків зони і види ризиків для підприємств олійно-жирової галузі в подальших дослідженнях будуть використані при розробці заходів щодо зниження ризиків.

Substantiated features of the analysis of oilseed enterprises' risks: identification of economic's risks factors, determination of their levels, identification of risks. The external and internal factors of economic risks are identified with their division into subjective and objective types and subsequent their classification. Three levels of potential risks are identified. The first level of risks according to the sphere of manifestation covers external and internal risks, at the second level risks are divided according to the nature of the occurrence into objective and subjective risk groups. The third level make subgroups of risks. The types of risks are identified by building a tree of external and internal subjective risks, a tree of external and internal objective risks The peculiarities of the quantitative risk analysis are determined: the choice of methods for quantitative assessment of risks, the assessment of enterprise riskiness and the identification of risk areas. The using of the statistical and expert method in risk analysis is justified. As statistical indicators is used average net profit (loss), variance, standard deviation, coefficient of variation. The calculated indicators of the expert assessment of risks: The probability of occurrence and degree of risks subgroups’ influence at oilseed enterprises; a generalized assessment of the probability of occurrence and the risk types impact’s degree; risk ranking; integral assessment of the degree of risk impact on the activities of enterprises. Zones and types of risks for enterprises of oilseed industry were established and it will be used in the development of anti-risk measures in subsequent studies.
Features of qualitative and quantitative risk’s analysis of oilseed companies
Keywords: фактори ризиків; ідентифікація ризиків; аналіз економічних ризиків; ступінь впливу; ризикозахищенність підприємств; зона; метод кількісної оцінки; probability of occurrence; degree of influence